Securities for bankers' advances - Holden, James Milnes (London : Pitman Publishing, 1971)
Detailed examination of valuation problems, interior of the house and inspection of the exterior of the properties.
Includes bibliographical references and index.
sju 23/01/2019
Loans
Keywords: Security (Law)